2002
DOI: 10.1002/cncr.10837
|View full text |Cite
|
Sign up to set email alerts
|

A lymph node metastatic mouse model reveals alterations of metastasis‐related gene expression in metastatic human oral carcinoma sublines selected from a poorly metastatic parental cell line

Abstract: BACKGROUNDGreater than 40% of patients with squamous cell carcinoma (SCC) of the oral cavity have lymph node metastasis at the time of diagnosis and a 5‐year survival rate of less than 50%. Changes in gene expression that regulate metastasis of SCC to lymph nodes have not been identified.METHODSTo study metastasis of oral SCC, highly metastatic oral SCC cell lines from a poorly metastatic oral SCC cell line were established by in vivo selection using a lymph node metastatic mouse model. The metastatic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 31 publications
5
75
1
Order By: Relevance
“…By using these cell lines, we observed that PAR-1 was significantly down-regulated in the selected highly metastatic cell lines as compared with their poorly metastatic parental cell line (24). Our current study complements this previous work by extending PAR-1 expression studies to human tumor tissues.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…By using these cell lines, we observed that PAR-1 was significantly down-regulated in the selected highly metastatic cell lines as compared with their poorly metastatic parental cell line (24). Our current study complements this previous work by extending PAR-1 expression studies to human tumor tissues.…”
Section: Introductionsupporting
confidence: 77%
“…To test this hypothesis, we initially examined the expression of the differentiation marker, involucrin, in the highly metastatic cell lines 686LN-M3a3 and 686LN-M3b3 established from the lymph node metastasis mouse model. These cell lines expressed lower PAR-1 than their poorly metastatic parental cell line 686LN (24). We found that the expression of involucrin was significantly down-regulated in highly metastatic cell lines as compared with 686LN (Fig.…”
Section: Correlation Of Par-1 Expression With a Differentiationmentioning
confidence: 68%
See 3 more Smart Citations